Sleep does not cause false memories on a story-based test of suggestibility - Mark Blagrove (Consciousness and Cognition, 2017)
Sleep contributes to the consolidation of memories. This process may involve extracting the gistof learned material at the expense of details. It has thus been proposed that sleep might lead tofalse memory formation. Previous research examined the effect of sleep on false memory usingthe Deese-Roediger-McDermott (DRM) paradigm. Mixed results were found, including increasesand decreases in false memory after sleep relative to wake. It has been questioned whether DRMfalse memories occur by the same processes as real-world false memories. Here, the effect of sleepon false memory was investigated using the Gudjonsson Suggestibility Scale. Veridical memorydeteriorated after a 12-h period of wake, but not after a 12-h period including a night’s sleep. Nodifference in false memory was found between conditions. Although the literature supports sleepdependentmemory consolidation, the results here call into question extending this to a gist-basedfalse memory effect.